Calcareous open sedge swards and stony grasslands (Seslerietalia caeruleae) on the northeren edge of the Trnosvki gozd plateau (the Dinaric mountains, western Slovenia) - Dakskobler, Igor (Hacquetia, 2015)
Applying the standard Central-European phytosociological method we studied the open sedge swards and stony grasslands on the northern edge of the Trnovski gozd plateau in western Slovenia. Based on extensive comparisons with similar communities in the Southeastern Alps and in the northern part of the Dinaric mountains we classified the studied communities into the order Seslerietalia caeruleae Br.-Bl. in Br.-Bl. & Jenny 1926. They are differentiated from similar communities in the Southeastern Alps by certain northern-Illyrian endemics (above all by Primula carniolica and Hladnikia pastinacifolia) and by some of the southern or southeastern-Alpine-Illyrian species (e.g. Phyteuma scheuchzeri subsp. columnae, Astrantia carniolica and Aquilegia bertolonii). This article describes these communites as the following new syntaxa: Primulo carniolicae-Seslerietum calcariae, Primulo carniolicae-Caricetum firmae, Caricetum mucronatae var. geogr. Primula carniolica and Caricetum ferrugineae var. Astrantia carniolica.